2011
DOI: 10.1007/s12070-011-0389-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Delayed Presentation of Congenitally Hearing Impaired Children in Rural India

Abstract: A study was conducted to determine why there was a delay in detection of hearing loss in congenitally hearing impaired children in rural India. It was found that although the parents of these children visited a primary care physician, relevant information regarding investigation and rehabilitation of hearing loss was not available to the patient. In the absence of a universal hearing screening programme in this country, it is a matter of importance to strengthen this aspect of community otolaryngology in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Parent’s literacy, father’s occupation, consangiuos marriage, socioeconomic status and geographical location of the family determined the age of diagnosis [ 7 ]. A prior study by Chary et al [ 8 ] in rural Karnataka, India showed the age of hearing loss recognition between 24 and 36 months.…”
Section: Discussionmentioning
confidence: 99%
“…Parent’s literacy, father’s occupation, consangiuos marriage, socioeconomic status and geographical location of the family determined the age of diagnosis [ 7 ]. A prior study by Chary et al [ 8 ] in rural Karnataka, India showed the age of hearing loss recognition between 24 and 36 months.…”
Section: Discussionmentioning
confidence: 99%
“…Newborn hearing screening is the main way to quickly detect neonatal hearing impairment in the early stage. In the absence of hearing screening, moderate to severe hearing loss is usually detected between 1 and 2 years of age, while mild hearing loss is only detected before school age 5,6 . However, the most worrying issue for newborn hearing screening is its false positive rate of 3%‐8%, which may cause persistent anxiety and adversely affect parent‐child relationships 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of hearing screening, moderate to severe hearing loss is usually detected between 1 and 2 years of age, while mild hearing loss is only detected before school age. 5 , 6 However, the most worrying issue for newborn hearing screening is its false positive rate of 3%‐8%, which may cause persistent anxiety and adversely affect parent‐child relationships. 7 , 8 , 9 Therefore, the selection of appropriate re‐screening strategy and time points are of great importance for newborns needed hearing re‐screening.…”
Section: Introductionmentioning
confidence: 99%